Delphi method applicability in drug foresight - Lintonen, Tomi; Karjalainen, Karoliina; Rönkä, Sanna; Kotovirta, Elina; Niemelä, Solja (BMC, 2025)
Background
The aim of the current study was to assess the accuracy of expert predictions, which were derived using a Delphi panel foresight study between 2009 and 2011, on a variety of drug-related topics in Finland in 2020.
Methods
The material used to evaluate the accuracy of the predictions consists of published reports on statistics, survey results, official register data, wastewater analyses and official documents. Whenever possible, we used multiple information sources to ascertain possible changes related to the predictions.
Results
Between 2009 and 2011, the majority - but not all - of the experts accurately predicted an increase in drug use. Indeed, more people experimented with or used drugs, and more drug residues were found in wastewater monitoring. The experts also correctly predicted an increase in population-level approval of drug use, but this development has been rather slow. Contrary to predictions, there was no marked increase in the use of new synthetic drugs. However, the misuse of buprenorphine increased during the 2010s. In the drug market, unit prices were surprisingly stable over the ten-year period. There were no changes in legislation related to the legal status of drugs, as was foreseen by the experts. However, enforcement moved in the direction foreseen by the experts: more lenient measures have been taken against users. Drug care system reforms favored a combination of mental health and addiction care units between 2009 and 2011, and 2020, as foreseen by the experts.
Conclusions
It seems to have been easier for the experts to foresee the continuation of existing trends, e.g., increasing use of drugs or widening approval of drugs, than to predict possible changes in the popularity of distinct groups of drugs such as new psychoactive substances (NPS). Even armed with the prediction that drug imports and wholesale would increasingly fall into the domain of organized crime, this undesirable development could not be stopped. Expert disagreement can also be seen as a valuable indication of uncertainty regarding the future. Foresight related to drug-related issues can produce relatively accurate and realistic views of the future at least up to ten years ahead.